2016
DOI: 10.1042/bsr20160151
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of angiotensin I-converting enzyme gene insertion/deletion polymorphism with rheumatic heart disease: a meta-analysis

Abstract: Rheumatic heart disease (RHD) is a serious cardiovascular disorder worldwide. Several articles have reported the effect of angiotensin I-converting enzyme gene insertion/deletion (ACE I/D) polymorphism in RHD risk. However, the results still remain inconsistent. The objective of the present study was to assess more precise estimations of the relationship between ACE I/D variant and RHD susceptibility. Relevant case–control studies published between January 2000 and 2016 were searched in the electronic database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…The ACE I/D SNP has been significantly associated with serum ACE activity (Zhang et al, ). The ACE gene (I/D) was recently reviewed by Tian et al, consistent with HuGENet™ review study design and recommendations (Tian et al, ). The meta‐analysis, which included the highest number of articles (nine), and a superior number of study participants (1,333 RHD cases and 1,212 controls), showed no association between ACE I/D and the risk of RHD (Tian et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ACE I/D SNP has been significantly associated with serum ACE activity (Zhang et al, ). The ACE gene (I/D) was recently reviewed by Tian et al, consistent with HuGENet™ review study design and recommendations (Tian et al, ). The meta‐analysis, which included the highest number of articles (nine), and a superior number of study participants (1,333 RHD cases and 1,212 controls), showed no association between ACE I/D and the risk of RHD (Tian et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The ACE gene (I/D) was recently reviewed by Tian et al, consistent with HuGENet™ review study design and recommendations (Tian et al, ). The meta‐analysis, which included the highest number of articles (nine), and a superior number of study participants (1,333 RHD cases and 1,212 controls), showed no association between ACE I/D and the risk of RHD (Tian et al, ). These results were in contrast with two previous meta‐analyses conducted in RHD cases: a meta‐analysis by Shang et al (), including six studies consisting a total of 981 RHD cases and 901 controls suggested that the ACE I/D SNP was significantly associated with RHD and a meta‐analysis conducted by Gupta et al, , which included four articles constituting 636 RHD cases and 533 controls reported a significant association between the ACE I/D and RHD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The angiotensin I-converting enzyme gene insertion/deletion polymorphism is another example of a locus showing different associations in different populations ( 50 , 51 ). A recent meta-analysis of nine studies including 1333 RHD cases and 1212 controls from seven different populations showed no correlation with the disease or disease subtypes ( 52 ).…”
Section: The Genetics Of Rhdmentioning
confidence: 99%
“…I/D polymorphism of АСЕ gene is associated with ACE blood level and determines the onset of such diseases as coronary heart disease, left ventricular hypertrophy, arterial hypertension, stroke, diabetic nephropathy, type 2 diabetes mellitus, diabetic nephropathy, diabetic neuropathy, diabetic retinopathy and hypertensive retinopathy, according to different research [ 35 , 38 – 46 ]. ACE gene D-alleles are believed to be a risk factor in these diseases.…”
Section: Introductionmentioning
confidence: 99%